Should sports scientists and coaches provide sodium supplementation to professional soccer players? Insights from English Premier League players - Foo, W. L.; Tester, E.; Markakis, P.; Sabou, V.; Close, G. L.; McCubbin, A. J.; Morton, J. P. (International Journal of Sports Science & Coaching, 2025)
We assessed the fluid balance, whole body sweat rate (WBSR) and sweat sodium concentration ([Na + ] sweat ) of English Premier League (EPL) soccer players during pre-season training and used predictive modelling to determine theoretical changes in plasma sodium concentration ([Na + ] plasma ). Players (25 ± 4 years, 1.83 ± 0.06 m, 81.1 ± 7.4 kg) were monitored during two training sessions (n = 14, Session 1; n = 17, Session 2) in temperate climates (19-23°C, 45-67% relative humidity). Training load was monitored via global positioning system, sweat loss was assessed from changes in body mass (BM) after correcting for fluid intake, and [Na + ] sweat was measured using absorbent patches. Mean BM loss was 1.08 ± 0.72% and 1.28 ± 0.65%, with sweat losses of 1.67 ± 0.49 L and 1.88 ± 0.59 L in Sessions 1 and 2, respectively. Mean [Na + ] sweat was 51.3 ± 14.6 mmol·L *1 (Session 1) and 39.9 ± 15.3 mmol·L *1 (Session 2), with total sodium losses of 1929 ± 771 mg and 1730 ± 813 mg, respectively. Predictive modelling indicated 4/14 (*29%) players in Session 1, and 1/17 (*6%) players in Session 2, would have mildly reduced [Na + ] plasma following training (all <2 mmol·L *1 ), due to either near-complete fluid replacement or high [Na + ] sweat . Although substantial interindividual variations were observed in fluid and sodium balance among players, modelling indicates that Na + supplementation is unnecessary for soccer players during training in a temperate climate. Measuring [Na + ] sweat is therefore unlikely to inform practical recommendations under these conditions.